Kerangka Teoritis Pengembangan Usaha Panti Asuhan: Meningkatkan Kesejahteraan Anak Melalui Manajemen Berbasis Prinsip - Iswanto, Juni (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
This article discusses the management of business units in orphanages as an effort to improve the welfare of the children living in them. The aim of this research is to analyze the management principles applied in the management of business units and their impact on child welfare. The method used in this study is a qualitative approach with a literature review and a case analysis of orphanages that have successfully managed business units. The results show that the application of effective management principles, such as strategic planning, good organization, and solid financial management, contributes to the increase in income and skills of the children. In addition, ongoing welfare evaluation can help orphanages identify areas that need improvement. Thus, the management of business units in orphanages not only meets the basic needs of children but also empowers them for a better future.